Correction to: Fetal macrosomia and its associated factors among singleton live-births in private clinics in Mekelle city, Tigray, Ethiopia - Freweini Gebrearegay Tela; Afework Mulugeta Bezabih; Amaha Kahsay Adhanu; Kidanemaryam Berhe Tekola (BMC, 2019)
Following publication of the original article [1], we have been notified that the name of one author was spelled incorrectly as Kidanemariam Berhe Tekola, when the correct spelling is Kidanemaryam Berhe Tekola.